Characteristics of cases of sexual violence that occurred in Alagoas between 2007-2016 - Elaine Calumby Teixeira; Alessandra Plácido Lima Leite; William Henrique Moreira dos Santos; José Humberto Belmino Chaves; Iasmin de Albuquerque Cavalcanti Duarte; Jairo Calado Cavalcante (O Mundo da Saúde, 2019)
Sexual violence stands out nationally as it is an important public health problem. Despite vitalizing various social segments, its incidence in historically vulnerable groups reflects a rooted patriarchal culture and gender violence. Although government efforts have advanced the quality of assistance, there are still omissions in the completeness of support. Thus, this study aimed to characterize the clinical and sociodemographic profile of female victims of sexual violence treated at a referral center in Alagoas during the period 2007-2016. Analytical cross-sectional study of historical series was performed with secondary data for the analysis of 920 records of care collected between August/2017 to December/2018 in the referral center for women's health located in Maceió, Alagoas. The profile of the victims was characterized as adolescents (57.0%), brown (68.5%), single (80.8%), students (59.6%) and those who had completed elementary school (51.3%). The most frequent type of violence was rape (96.5%), committed at home (39.4%), by a single aggressor (85.9%), during the nighttime (43.1%). Extra-family violence predominated (87.9%) with an unknown perpetrator (59.4%). In the intrafamilial forms, stepfather (4.0%) and father (3.2%) were the main perpetrators. Pregnancy as a consequence of violence was present in only 2.8% of cases. However, the minority managed to perform legal abortion in the institution (31.8%). This study highlights the profile of victims of sexual violence in Alagoas through a descriptive approach focusing on the various factors surrounding it.